2004
DOI: 10.1103/physrevc.69.064317
|View full text |Cite
|
Sign up to set email alerts
|

Instability of nuclear wobbling motion and tilted axis rotation

Abstract: We study a possible correspondence between the softening of the wobbling mode and the "phase transition" of the one-dimensionally rotating mean field to a three-dimensionally rotating one by comparing the properties of the wobbling mode obtained by the one-dimensional cranking model + random phase approximation with the total routhian surface obtained by the three-dimensional tilted-axis cranking model. The potential surface for the observed wobbling mode excited on the triaxial superdeformed states in 163 Lu … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…(18) if the relation between γ (pot:Nils) and γ (den) is taken into account. The excitation energy can be expressed in terms of the three moments of inertia in a usual way [7,30], but their γ dependence is not like the irrotational inertia [37,40], which leads to the rather weak γ dependence of the excitation energy. Here we have only shown the example of the wobbling excitation in 163 Lu, but we have confirmed that these properties of the wobbling-like RPA solution are general, and can be applied to other cases in the Lu region.…”
Section: B(e2) Ratio Of the Wobbling Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…(18) if the relation between γ (pot:Nils) and γ (den) is taken into account. The excitation energy can be expressed in terms of the three moments of inertia in a usual way [7,30], but their γ dependence is not like the irrotational inertia [37,40], which leads to the rather weak γ dependence of the excitation energy. Here we have only shown the example of the wobbling excitation in 163 Lu, but we have confirmed that these properties of the wobbling-like RPA solution are general, and can be applied to other cases in the Lu region.…”
Section: B(e2) Ratio Of the Wobbling Bandmentioning
confidence: 99%
“…[38,39]. The instability of the wobbling excitation was also studied [40] in relation to the tilted axis cranking rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mean-filed approximation, cranking model yields only the yrast sequence for a given configuration, Therefore, in order to describe the wobbling excitations, one has to go beyond the mean-filed approximation. At present, this has been done by incorporating the quantum correlations by means of random phase approximation (RPA) [21][22][23][24][25][26][27][28] or by the generator coordinate method after angular momentum projection (GCM+AMP) based on the cranking intrinsic states [29].…”
Section: Introductionmentioning
confidence: 99%
“…[13]. Furthermore, the rotational bands built on the high-K multiquasiparticle states can be interpreted theoretically as a multiphonon excitation of the precession mode, which is the axially symmetric limit of the wobbling mode [14].…”
Section: Introductionmentioning
confidence: 99%